2023
DOI: 10.1136/bmjopen-2022-069345
|View full text |Cite
|
Sign up to set email alerts
|

Association between BUN/creatinine ratio and the risk of in-hospital mortality in patients with trauma-related acute respiratory distress syndrome: a single-centre retrospective cohort from the MIMIC database

Abstract: ObjectiveRecent studies have shown that blood urea nitrogen to creatinine (BUN/Cr) ratio might be an effective marker for the prognosis of patients with respiratory diseases. Herein, we aimed to assess the association between BUN/Cr ratio and the risk of in-hospital mortality in patients with trauma-related acute respiratory distress syndrome (ARDS).DesignA retrospective cohort study.Setting and participants1034 patients were extracted from the Medical Information Mart for Intensive Care-III (MIMIC-III) databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The BCR is a straightforward and readily obtainable measure, as it relies solely on venous blood samples in clinical settings. Previous studies have reported an association between the BCR and in-hospital mortality in various diseases (17)(18)(19)(20). BCR, a biomarker of neurohormonal activity, has been associated with poor prognosis in patients with acute heart failure and is an independent predictor of all-cause mortality (31).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The BCR is a straightforward and readily obtainable measure, as it relies solely on venous blood samples in clinical settings. Previous studies have reported an association between the BCR and in-hospital mortality in various diseases (17)(18)(19)(20). BCR, a biomarker of neurohormonal activity, has been associated with poor prognosis in patients with acute heart failure and is an independent predictor of all-cause mortality (31).…”
Section: Discussionmentioning
confidence: 99%
“…Their investigation revealed that a higher BUN/Cr ratio served as an independent prognostic indicator for both the COVID-19 severity and patient outcomes related to survival. Ma et al ( 20 ) conducted a recent investigation to elucidate the association between the BUN/Cr ratio and in-hospital mortality among patients diagnosed with trauma-induced acute respiratory distress syndrome. Their findings revealed a statistically significant correlation between elevated BUN/Cr ratios and an increased risk of death within the hospital setting for these patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation